Sinkronisasi Sistem Perencanaan Pembangunan Nasional melalui Pemilihan Umum Serentak - Yusri; Aris Nur Qadar Ar Razak; Aris Darmawan Al-Habib (Institut Agama Islam (IAIN) Kendari, 2026)
The simultaneous general elections in 2024 have significant relevance to long-term development planning, particularly during the RPJPN period of 2025-2045. However, the misalignment between political cycles and development planning cycles has caused fragmentation in policy between the central and regional governments. This study aims to analyze the impact of synchronized elections on the integration of central and regional policies to achieve consistent national development goals. The research design uses a literature review approach, examining laws, journals, and other relevant sources, and applying policy analysis to describe the challenges and opportunities of such synchronization. The findings indicate that synchronized elections have the potential to improve the harmony of national development implementation, reduce regional disparities, and strengthen political stability. However, challenges remain in the timing alignment between the elections and the preparation of RPJMD. A limitation of this research is the absence of empirical data that could directly support field analysis. The added value of this study lies in its contribution to formulating policy recommendations to enhance the effectiveness of synchronized elections as an instrument for sustainable development, as well as offering a new perspective on the relationship between democratic legitimacy and development consistency. This study is expected to contribute to the development of public policy theory and national development planning in Indonesia.